2014
DOI: 10.2215/cjn.12281211
|View full text |Cite
|
Sign up to set email alerts
|

Change in Albuminuria and eGFR Following Insulin Sensitization Therapy Versus Insulin Provision Therapy in the BARI 2D Study

Abstract: SummaryBackground and objectives In the Bypass Angioplasty Revascularization Investigation 2 Diabetes randomized trial, glycemic control with insulin-sensitization therapy was compared with insulin-provision therapy in patients with type 2 diabetes and coronary artery disease. This study examined differences in albumin excretion and renal function in the insulin-sensitization group versus the insulin-provision group over 5 years.Design, setting, participants & measurements In total, 1799 patients with measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…Since insulin sensitivity can be modified by both lifestyle changes (diet and exercise) and drugs such as metformin, improved insulin sensitivity holds promise as a therapeutic target to reduce DN in adolescents with type 2 diabetes. The BARI-2D study ( 33 ) showed no benefit of insulin sensitizing strategy on DN in older adults with coronary artery disease and type 2 diabetes, but with a mean age of 62 years and most participants having both hypertension and hyperlipidemia, this is a very different study population than ours ( 34 ). The renal injury in longstanding nephropathy in older adults with multiple cardiovascular risk factors may also be less responsive to changes in insulin sensitivity than the early alterations in renal function seen in adolescents with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 60%
“…Since insulin sensitivity can be modified by both lifestyle changes (diet and exercise) and drugs such as metformin, improved insulin sensitivity holds promise as a therapeutic target to reduce DN in adolescents with type 2 diabetes. The BARI-2D study ( 33 ) showed no benefit of insulin sensitizing strategy on DN in older adults with coronary artery disease and type 2 diabetes, but with a mean age of 62 years and most participants having both hypertension and hyperlipidemia, this is a very different study population than ours ( 34 ). The renal injury in longstanding nephropathy in older adults with multiple cardiovascular risk factors may also be less responsive to changes in insulin sensitivity than the early alterations in renal function seen in adolescents with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 60%
“…metformin), IS may be a promising therapeutic target to reduce DKD in adolescents with T2D. In adults with coronary artery disease and T2D (41), BARI-2D (Bypass Angioplasty Revascularization Investigation in Type 2 Diabetes) insulin-sensitizing therapy had no benefit on progression of DKD. However, this study population was significantly different than the TODAY cohort, with a mean participant age of 62 years and most participants already having hypertension and hyperlipidemia at baseline (42).…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Institutional Review Boards at each participating site and all participants gave written informed consent. Details of study design, characteristics of the study population, baseline kidney function, change in albuminuria following therapy, and primary outcome have been reported previously. The dataset used in this post hoc analysis was obtained from BioLINCC (The National Heart, Lung, and Blood Institute Biologic Specimen and Data Repository Information Coordinating Center) in Excel (Microsoft, Redmond, WA) format for a retrospective study based on uACR.…”
Section: Methodsmentioning
confidence: 99%